2009
DOI: 10.1017/s0007114509371743
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of markers of bone resorption by consumption of vitamin D and calcium-fortified soft plain cheese by institutionalised elderly women

Abstract: Acceleration of bone remodelling increases the risk of fragility fractures. The objective of the present study was to explore in elderly women whether a vitamin D and Ca-fortified dairy product providing about 17-25 % of the recommended intakes in vitamin D, Ca and proteins would reduce secondary hyperparathyroidism and bone remodelling in a way that may attenuate age-related bone loss in the long term. Thirty-seven institutionalised women, aged 84·8 (SD 8·1) years, with low serum 25-hydroxyvitamin D (5·5 (SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 13 publications
6
37
0
Order By: Relevance
“…A Swiss study confirmed that the dietary intervention, namely the administration of dairy products enriched in calcium and vitamin D, was reflected by a decreased serum level of biomarker of bone resorption 5b TRAP in postmenopausal women; this pointed to a nutrition-related decrease in the rate of bone mass involution [16,17]. Our group included 2.0% of women with confirmed osteoporosis.…”
Section: H -High M -Moderate L -Low Level Of Self-efficacy (Gses)/osupporting
confidence: 68%
“…A Swiss study confirmed that the dietary intervention, namely the administration of dairy products enriched in calcium and vitamin D, was reflected by a decreased serum level of biomarker of bone resorption 5b TRAP in postmenopausal women; this pointed to a nutrition-related decrease in the rate of bone mass involution [16,17]. Our group included 2.0% of women with confirmed osteoporosis.…”
Section: H -High M -Moderate L -Low Level Of Self-efficacy (Gses)/osupporting
confidence: 68%
“…Milk consumption has been shown to favorably affect bone remodeling in postmenopausal women (22,23) and in elderly (24). in an open study carried out in institutionalized vitamin D deficient women, we observed an apparent beneficial effect on bone turnover markers after 4 weeks of soft plain cheese consumption, providing about 17-25 % of the recommended daily intakes of vitamin D, calcium and proteins (25).…”
Section: Introductionmentioning
confidence: 60%
“…hip fracture incidence is particularly elevated in nursing home residents, as observed in several countries (36)(37)(38). We recently reported results of an open trial exploring whether consumption of vitamin D and calcium enriched soft plain cheese may modify bone turnover in a way expected to attenuate the rate of bone loss among institutionalized elderly women (25). the results of this exploratory study suggested that fortified soft plain cheese consumed during one month by elderly women with vitamin D insufficiency can reduce bone resorption markers, namely ctX and traP 5b, by positively influencing ca and protein economy, as expressed by decreased Pth and increased iGF-i, respectively (25).…”
Section: Participants and Designmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Bonjour et al (2009), fortified soft plain cheese consumed by elderly women with vitamin D insufficiency can decrease bone resorption markers by positively influencing calcium and protein economy, as expressed by decreased parathyroid hormone and increased IGF-I, respectively. Such a dietary intervention might uncouple, at least transiently, bone resorption from bone formation and thereby attenuate age-related bone loss.…”
Section: Fortified Dairy Productsmentioning
confidence: 99%